Herschel deep far-infrared counts through Abell 2218 cluster-lens - Altieri, B; Berta, S; Lutz, D; Kneib, J; Metcalfe, L; Andreani, P; Aussel, H; Bongiovanni, A; Cava, A; Cepa, J; Ciesla, L; Cimatti, A; et al. (2010)
Gravitational lensing by massive galaxy clusters allows study of the population of intrinsically faint infrared galaxies that lie below the sensitivity and confusion limits of current infrared and submillimeter telescopes. We present ultra-deep PACS 100 and 160 μm observations toward the cluster lens Abell 2218 to penetrate the Herschel confusion limit. We derive source counts down to a flux density of 1 mJy at 100 μm and 2 mJy at 160 μm, aided by strong gravitational lensing. At these levels, source densities are 20 and 10 beams/source in the two bands, approaching source density confusion at 160 μm. The slope of the counts below the turnover of the Euclidean-normalized differential curve is constrained in both bands and is consistent with most of the recent backwards evolutionary models. By integrating number counts over the flux range accessed by Abell 2218 lensing (0.94-35 mJy at 100 μm and 1.47-35 mJy at 160 μm), we retrieve a cosmic infrared background surface brightness of ∼8.0 and ∼9.9 nW m-2 sr -1, in the respective bands. These values correspond to 55±24% and 77±31% of DIRBE direct measurements. Combining Abell 2218 results with wider/shallower fields, these figures increase to 62±25% and 88±32% CIB total fractions, resolved at 100 and 160 μm, disregarding the high uncertainties of DIRBE absolute values. © 2010 ESO.